1999
DOI: 10.1046/j.1365-2168.1999.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Kupffer cell response to exogenous endotoxin in a rodent model of obstructive jaundice

Abstract: These data demonstrate simultaneous impairment of Kupffer cell clearance of endotoxin and increased secretion of proinflammatory cytokines in experimental obstructive jaundice. These diverse responses may contribute to the development of sepsis-related complications in biliary obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 37 publications
3
17
0
4
Order By: Relevance
“…Our model differs from other models of bile duct obstruction in the literature (2,9,10,19,22,23). These models have focused on late time points (1 to 3 weeks) after bile duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Our model differs from other models of bile duct obstruction in the literature (2,9,10,19,22,23). These models have focused on late time points (1 to 3 weeks) after bile duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…18,23 After endotoxin administration to cholestatic rats, Kennedy et al demonstrated that blockade of Kuppfer cells with gadolinium chloride leads to a lower systemic TNF activity and subsequently resulted in an improved survival. 17 On the other hand, the enhanced IL-6 release, as found in jaundiced mice exposed to endotoxin, might actually play an important role in protecting the cholestatic host against hypersensitivity to endotoxin and was found to abrogate cholestatic liver injury. 22,24 In the perspective of these results found in animal models of biliary obstruction, it appears that the generalized inflammatory state in patients with obstructive jaundice was profoundly different.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…[17][18][19][20][21][22] Increased concentrations of TNF, mainly produced by liver Kuppfer cells, or rather, the imbalance with its soluble receptors, as antagonists and released from the cell membrane by endotoxemia, are suggested to contribute to development of complications. 18,23 After endotoxin administration to cholestatic rats, Kennedy et al demonstrated that blockade of Kuppfer cells with gadolinium chloride leads to a lower systemic TNF activity and subsequently resulted in an improved survival.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Numerous experimental studies have demonstrated a profound proinflammatory response following endotoxin challenge, which is marked by an increased production of tumor necrosis factor (TNF)-␣, interleukin (IL)-1, and IL-6 in animals with biliary obstruction (9,14,17,18,28). This proinflammatory milieu is associated with increased markers of end organ injury [aspartate aminotransferase (AST) and creatinine] and death (14), and blockade of this response through the administration of gadolinium chloride has been shown to suppress the systemic proinflammatory response leading to improved survival (18,24).…”
mentioning
confidence: 99%